2015
DOI: 10.3897/zookeys.487.9176
|View full text |Cite
|
Sign up to set email alerts
|

No need to replace an “anomalous” primate (Primates) with an “anomalous” bear (Carnivora, Ursidae)

Abstract: By means of mitochondrial 12S rRNA sequencing of putative “yeti”, “bigfoot”, and other “anomalous primate” hair samples, a recent study concluded that two samples, presented as from the Himalayas, do not belong to an “anomalous primate”, but to an unknown, anomalous type of ursid. That is, that they match 12S rRNA sequences of a fossil Polar Bear (Ursus maritimus), but neither of modern Polar Bears, nor of Brown Bears (Ursus arctos), the closest relative of Polar Bears, and one that occurs today in the Himalay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…[ 37 ] suggested that a previously unrecognized bear species or possibly a hybrid between brown bear and polar bear exists in the Himalayas. However, as also demonstrated by others [ 39 , 40 ], the short 12S rRNA gene fragment is insufficiently informative to determine precise taxonomic identity, particularly among closely related species, although it can be a useful screening marker to assess preliminary species affinities. We isolated DNA and assembled a complete mitogenome from a hair sample (collected in Ladakh, India, and named ‘YHB’ in this study), which based on their shared collection locality and other anecdotal evidence obtained from Icon Films, our sample source, may come from the same specimen that Sykes et al [ 37 ] speculated represents an unknown or hybrid bear.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…[ 37 ] suggested that a previously unrecognized bear species or possibly a hybrid between brown bear and polar bear exists in the Himalayas. However, as also demonstrated by others [ 39 , 40 ], the short 12S rRNA gene fragment is insufficiently informative to determine precise taxonomic identity, particularly among closely related species, although it can be a useful screening marker to assess preliminary species affinities. We isolated DNA and assembled a complete mitogenome from a hair sample (collected in Ladakh, India, and named ‘YHB’ in this study), which based on their shared collection locality and other anecdotal evidence obtained from Icon Films, our sample source, may come from the same specimen that Sykes et al [ 37 ] speculated represents an unknown or hybrid bear.…”
Section: Discussionmentioning
confidence: 98%
“…Based on a short fragment of the mtDNA 12S rRNA gene from two samples collected in Ladakh, India and Bhutan, respectively, and a 100% match to a sequence recovered from a subfossil polar bear [ 38 ], Sykes et al [ 37 ] speculated that an unclassified bear species or hybrid of polar bear and brown bear might be present in the Tibetan Plateau–Himalaya region. However, this speculation was critiqued by others [ 39 , 40 ], and their phylogenetic analyses using the sequences from Sykes et al and other available Ursidae sequences did not rule out the possibility that the samples belonged to brown bear. Thus, to get accurate species identification, comprehensive phylogenetic analyses using genetic information from more variable and informative loci are needed.…”
Section: Introductionmentioning
confidence: 99%
“…Further, the phylogenetic relationships of some ursid taxa in our sample are unresolved. (Kutschera et al, 2014), and the positioning of U. thibetanus as the basal ursine, with H. malayanus and U. americanus as sister taxa (Gutiérrez and Pine, 2015).…”
Section: Statistical Analysesmentioning
confidence: 96%